Corporate Social Responsibility, Reputation, and Financial Performance - Kurniawan, Muhammad Aditya; Munandar, Agus (Syntax Corporation, 2025)
Nowadays, many companies have implemented CSR programs as a business strategy, where they build community empowerment facilities in the areas of their operations. CSR can be defined as a commitment demonstrated by a company to provide contributions to the sustainable economic development process, prioritizing attention to environmental, economic, and social aspects. This research aims to investigate the relationship between corporate social responsibility (CSR), company reputation, and their influence on the financial performance. The research employs a quantitative approach and collects data from 2019 to 2021 from companies listed on the ESG Quality 45 IDX KEHATI index. CSR is measured through sustainability practice indicators using the Corporate Social Responsibility Index, while company reputation is evaluated through 5 dimensions of measurement. Financial performance is measured using financial ratios involving profitability, liquidity, and leverage. The analysis results indicate that, although there is no significant influence between CSR and company reputation, CSR practices have a significant impact on financial performance. This finding highlights the importance of CSR practices in enhancing the financial aspects of companies. While company reputation significantly affects financial performance, the research shows that reputation does not moderate the relationship between CSR and financial performance.